2017
DOI: 10.1073/pnas.1618101114
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis of KcsA potassium channel's activation– deactivation gating is caused by structural changes at the channel’s selectivity filter

Abstract: Mode-shift or hysteresis has been reported in ion channels. Voltageshift for gating currents is well documented for voltage-gated cation channels (VGCC), and it is considered a voltage-sensing domain's (VSD) intrinsic property. However, uncoupling the Shaker K + channel's pore domain (PD) from the VSD prevented the modeshift of the gating currents. Consequently, it was proposed that an open-state stabilization of the PD imposes a mechanical load on the VSD, which causes its mode-shift. Furthermore, the mode-sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 50 publications
9
42
0
Order By: Relevance
“…It is known that the VSD communicates with a pore via its linker to the gate, and it is also known that the gate communicates with the selectivity filter 21,63,71 . To our knowledge, there is no previous evidence of communication between the VSD and the pore via the interface between them.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is known that the VSD communicates with a pore via its linker to the gate, and it is also known that the gate communicates with the selectivity filter 21,63,71 . To our knowledge, there is no previous evidence of communication between the VSD and the pore via the interface between them.…”
Section: Discussionmentioning
confidence: 99%
“…Some channels rely on large intracellular domains or auxiliary subunits for their correct function. Since the importance and function of the segments in gating varies between channels, it is also likely that the communication between these segments varies, which different studies have confirmed [22][23][24][25][26][27][28]58,60,63,71 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hysteresis phenomenon is ubiquitous in optical devices [16], many-body systems [8], and biological systems [7]. In recent years, there has been a growing interest in understanding hysteretic response of ion channels to varying applied voltages [3,9,14,31,44,48,51,60]. Hysteresis of ions channels is of physiological significance, since it involves many human physiological processes [9,44,60].…”
Section: Introductionmentioning
confidence: 99%